The Analysis of Challenges and Opportunities in Integrated Village Government (IVG) - Haeruddin, Haeruddin; Putera, Roni Ekha; Mohamed, Nabilaa (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
Following the implementation of the Law of Village, the resolution of village government issues proved to be a challenging endeavour. This paper presents a comprehensive systematic analysis to identify themes in village government studies. The primary objective is categorising the problems and possibilities village governments encounter. The research data utilised in this study is obtained from the Scopus Database, covering the period from 2009 to 2023. The data is subsequently analysed using the VOSviewer tool. The findings present five prominent themes and a total of 35 network elements of the governance of rural communities. These themes encompassed many aspects, such as healthcare, economic matters, conflicts, agricultural practices, and government initiatives. The study revealed that despite implementing the Law on Villages, the prevalence of intricate challenges in village government remains prominent. Scholars concur that they advocate for establishing collaborative efforts among stakeholders to delineate the sequential problem-solving steps. However, it is worth noting that rural communities often face challenges in embracing external interactions and adopting the urban commons model to establish an extensive network and facilitate multi-level growth. The findings serve as a foundation for future investigations on village government and a point of reference for more informed decision-making in governance practices. The limits were due to the exclusive use of publications from Scopus for analysis. Hence, conducting research employing a comparative approach and leveraging the Web of Science (WoS) database and other indexes are crucial to promoting the conceptual progress of village government study